Development of a PCR assay based on the 16S-23S rDNA internal transcribed spacer for identification of strictly anaerobic bacterium Zymophilus - Felsberg, Jurgen; Jelínková, Markéta; Kubizniaková, Petra; Matoulková, Dagmar (Anaerobe, 2015)
PCR-primers were designed for identification of strictly anaerobic bacteria of the genus Zymophilus based on genus-specific sequences of the 16S-23S rDNA internal transcribed spacer region. The specificity of the primers was tested against 37 brewery-related non-target microorganisms that could potentially occur in the same brewery specimens. None DNA was amplified from any of the non-Zymophilus strains tested including genera from the same family (Pectinatus, Megasphaera, Selenomonas), showing thus 100% specificity. PCR assay developed in this study allows an extension of the spectra of detected beer spoilage microorganisms in brewery laboratories.
Keywords: Bacteria, Anaerobic; anaerobní bakterie; intergenová DNA; RNA ribozomální; Anaerobiosis; Base Sequence; DNA, Intergenic; molekulární sekvence - údaje; Molecular Sequence Data; anaerobióza; RNA, Ribosomal; Sensitivity and Specificity; polymerázová řetězová reakce; Polymerase Chain Reaction; Sequence Alignment; sekvenční seřazení; senzitivita a specificita; sekvence nukleotidů